The ten-thousand year fever rethinking human and wild primate malarias - Cormier, Loretta A.; ebrary, Inc. (Walnut Creek, Calif. : Left Coast Press, 2011)
"Malaria is one of the oldest recorded diseases in human history, and its 10,000-year relationship to primates can teach us why it will be one of the most serious threats to humanity in the 21st century. In this pathbreaking book Loretta Cormier integrates a wide range of data from molecular biology, ethnoprimatology, epidemiology, ecology, anthropology, and other fields to reveal the intimate relationships between culture and environment that shape the trajectory of a parasite. She argues against the entrenched distinction between human and non-human malarias, using ethnoprimatology to develop a new understanding of cross-species exchange. She also shows how current human-environment interactions, including deforestation and development, create the potential for new forms of malaria to threaten human populations. This book is a model of interdisciplinary integration that will be essential reading in fields from anthropology and biology to public health"--
Machine generated contents note: Preface 1. Malaria as a Primate Disorder 2. Co-Evolution: Parasites, Vectors, and Hosts 3. Falciparum-Type: The Chimpanzee Malaria 4. Vivax-Type: The Macaque Malaria 5. Migration: Malaria in the New World 6. Rhesus Factor: Experimental Studies in Wild Primates 7. Ethics: Human Experimentation 8. Future: The Primate Malaria Landscape Appendix I. Plasmodia Parasites and their Natural Primate Hosts Appendix II. Experimentally-Induced Plasmodium Cross-Infections into Novel Hosts Appendix III. Naturally-Acquired Cross-Infections with Novel Malaria Parasites Appendix IV. Primate Species and All Infections with Plasmodium Parasites References Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Malaria; Medical parasitology; Primates -- Diseases; Electronic books